Combined Analytical and Numerical Approach to Study Coil Arrays for Contactless Charging of Batteries in Active Transponders - Hrebenciuc, F. A.; Moga, D.; Petreus, D.; Barabas, Z.; Moga, R. (Elektronika ir Elektrotechnika, 2012)
This paper introduces a combined analytical and numerical approach in order to study the suitability of a coil array for contactless transfer of the energy needed for the charging of batteries in active transponders. The way in which the geometry of the coil system influences the efficiency of the transfer is analyzed based on flux computation. An array of planar, circularly shaped primary coils is proposed as a solution to transmit the energy to a secondary coil, contained in the active tag, for situations of random placement of the active tag above the coil array. Ill. 19, bibl. 13 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.123.7.2372